Functional reprogramming of peripheral blood monocytes by soluble mediators in patients with pancreatic cancer and intraductal papillary mucinous neoplasms - Eckhoff, Austin M.; Brown, Michael C.; Landa, Karenia; Naqvi, Ibtehaj; Holl, Eda K.; Boczkowski, David; Fletcher, Ashley; Rhodin, Kristen E.; Giang, Minh Huy; Sullenger, Bruce; Beasley, Georgia M.; Allen, Peter J.; et al. (Frontiers in Immunology, 2023)
Background: Monocytes and monocyte-derived tumor infiltrating cells have been implicated in the immunosuppression and immune evasion associated with pancreatic adenocarcinoma (PDAC). Yet, precisely how monocytes in the periphery and tumor microenvironment in patients with intraductal papillary mucinous neoplasm (IPMN), a precursor lesion to PDAC, change during disease progression has not been defined. Here we functionally profiled the peripheral immune system and characterized the tumor microenvironment of patients with both IPMN and PDAC. We also tested if sera from patients with IPMN and PDAC functionally reprogram monocytes relative to that of healthy donors.Methods: Pancreatic tissue and peripheral blood were collected at the time of resection from 16 patients with IPMN and 32 patients with PDAC. Peripheral blood and pancreatic tissue/tumor were immunophenotyped using flow cytometry. Whole blood was plated and incubated with R848 (a TLR 7/8 agonist) or LPS (a TLR4 agonist) for 6 hours and TNF expression in monocytes was measured by flow cytometry to measure monocyte activation. To test if TLR sensitivity is determined by factors in patient sera, we preconditioned healthy donor monocytes in serum from PDAC (n=23), IPMN Monocyte Tolerance in IPMN 2 (n=15), or age-matched healthy donors (n=10) followed by in vitro stimulation with R848 or LPS and multiplex cytokine measurements in the supernatant.Results: TNF expression in R848-stimulated peripheral blood monocytes was higher in patients with low grade vs high grade IPMN (65% vs 32%, p = 0.03) and stage 1 vs stage 2/3 PDAC (58% vs 42%, p = 0.03), this was not observed after LPS stimulation. TLR activation correlated with increasing grade of dysplasia from low grade IPMN to high grade IPMN. Serum from patients with IPMN and PDAC recapitulated suppression of TNF induction after R848 stimulation in naïve, healthy donor monocytes.Peripheral blood monocyte TNF secretion inversely correlates with the degree of dysplasia in IPMN and cancer stage in PDAC, suggesting innate immune reprogramming as IPMNs progress to invasive disease. These effects are, at least in part, mediated by soluble mediators in sera.